Poetic Listening: For an Audiometry of recent Argentinean Poetry - Matías Moscardi (Estudios de Teoría Literaria, 2019)
In the current paper I propose, starting from an textual analysis with its corresponding and consigned audiovisual support, an introduction to Argentinean recent poetry (2010-2017) from an theoretical approach of listening as one of the unavoidable objects of contemporary criticism.